Shifting the focus of world industrial development from European countries and North America to Asia - A. V. Ivanchenko (Вестник университета)
Industry is the basis of economic development, therefore, studying the real sector allow us to assess the physical scale of the economy of individual countries and the world as a whole. The industrial production structural distribution by countries and macro-regions reflects the real balance of power in the global arena. Retrospective analysis allows us to see this process in dynamics, which contributes to the correct construction of models of further international cooperation, foreign trade and infrastructural development in this direction.   The purpose of the study is to assess the dynamics of the industrial production shift from West to East in recent decades.   The tabular, graphical and descriptive methods were used, and it allowed us to visualize the indicators retrospective analysis results. In the course of the work it has been proved that by now there is parity in the level of industrial production between the countries of the collective West and East. It makes it possible to change the term “developed countries” meaning and extend it not only to European and North American countries, but also to a number of Asian and Latin American countries due to the ever-growing importance of these countries’ industry on a global scale.